Graves Disease dengan Gangguan Irama Jantung - M Agung Yudistira Permana; Widyanto P Adhy; Nurmalinda Kurniasih Mappapa; Iriyanti Aderina Patola (Medula, 2020)
Hyperthyroidism is an endocrine disorder with the second highest incidence after diabetes, the most common hyperthyroidism (60% -80% of cases) is caused by Graves’ disease. Graves' disease is an autoimmune disorder, the presence of thyroid stimulating immunoglobulin (TSI), or can be called a thyroid stimulating antibody (TSAb) which is secreted in the thyroid gland binding to thyroid stimulating hormone (TSH) receptors in the thyroid gland to stimulate the thyroid gland to produce hormones . In this case, Ms. FF 47th came with thumping chest since one week before came to hospital, accompanied by excessive sweating and trembling hands. There is enlargement of the skin-colored, painless thyroid gland with no firm boundary. From TSH laboratory results <0.1 µU/mL, total T4 and T3 are 157 µg/dL and 8.9ng/dL accompanied by atrial fibrillation on the ECG. Given 3x100mg PTU therapy and oral 3x30mg propanolol obtained good results on the third day of treatment. A long evaluation and monitoring is needed to ensure that the patient has healing.